2016
DOI: 10.21776/ub.ruas.2016.014.02.7
|View full text |Cite
|
Sign up to set email alerts
|

Filosofi Penataan Ruang Spasial Vertikal Pada Rumah Tradisional Saoraja Lapinceng Kabupaten Barru

Abstract: ABSTRAKRumah tradisional Bugis secara vertikal pada umumnya dibagi atas tiga bagian yakni kepala, badan, dan kaki rumah. Ketiga bagian ini memiliki fungsi dan filosofi yang berbeda tetapi menjadi satu kesatuan yang saling bersinergi. Dalam bidang arsitektural, filosofi berperan sebagai penentu kebijakan pembagian ruang spasial pada bangunan. Utamanya pada bangunan tradisional seperti Saoraja Lapinceng di Kabupaten Barru yang memiliki beragam filosofi dan pesan yang bermakna yang dihasilkan dari penafsiran masy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
1
Order By: Relevance
“…Gender relations have also been found to be a determinant in the spatial arrangement of residential houses among the Sumba ethnic groups to show the gender duality dynamics of male and female which is centred on the living room as a family fireplace (Asih et al 2015). Another study showed gender category was also used in determining the vertical spatial structure in the traditional house of Saoraja Lapinceng in Barru Regency (Wasilah and Hildayanti 2016). Moreover, gender was also discovered to be playing a significant role in different aspects of life in the Tamkesi traditional village of Timor (Lake 2016;Tallo 2013) as well as Naga in West Java (Khairunnisa 2014).…”
Section: Gender In Culture and Architecturementioning
confidence: 99%
“…Gender relations have also been found to be a determinant in the spatial arrangement of residential houses among the Sumba ethnic groups to show the gender duality dynamics of male and female which is centred on the living room as a family fireplace (Asih et al 2015). Another study showed gender category was also used in determining the vertical spatial structure in the traditional house of Saoraja Lapinceng in Barru Regency (Wasilah and Hildayanti 2016). Moreover, gender was also discovered to be playing a significant role in different aspects of life in the Tamkesi traditional village of Timor (Lake 2016;Tallo 2013) as well as Naga in West Java (Khairunnisa 2014).…”
Section: Gender In Culture and Architecturementioning
confidence: 99%
“…Sesuai dengan tradisi dan kepercayaan masyarakat suku Bugis, terdapat adat istiadat berupa aturan dan pedoman dalam berpikir serta bertindak untuk menjalani hidup. Adat istiadat tersebut merupakan warisan yang diturunkan oleh nenek moyang terkait bagaimana cara bersosialiasi dengan masyarakat, cara bertata krama dan tata cara mendirikan rumah (Wasilah & Hildayanti, 2017). Warisan terkait ilmu dan tata cara mendirikan rumah tersebut telah diturunkan dalam bentuk lisan dan naskah tertulis secara turun temurun.…”
Section: Tradisi Membangun Rumah Masyarakat Suku Bugisunclassified
“…For example, Broadbent (1980), Howell (2013), Akil and Osman (2017), and Reed (2019) have reported the concept of space in a traditional or customary house to be a form of expression of identity and local cultural entities. This means the Bugis house, or Bola-Ugi, physically realized vertically on the stage as a form of local culture, reflects the natural conditions and culture of the Bugis people (Wasilah & Hildayanti, 2017;Naing, Hadi, & Djamereng, 2018;Artiningrum & Sukmajati, 2017). This concept has been in operation for generations as a value system in addition to its ability to provide comfort, safety, and harmony for the residents within the surrounding natural world (Naing, Hadi, & Djamereng, 2018).…”
Section: Introductionmentioning
confidence: 99%